PRODUCTIVE CAPACITY AND SUSTAINABLE DEVELOPMENT OF UKRAINE IN THE CONDITIONS OF WAR - Anatoliy Mokiy; Larysa Nozdrina; Andriy Pavlyshyn (Akademičnij Oglâd, 2024)
The article examines the state of Ukraine’s military economy and forecasts of its reconstruction. It is noted that one of the ways for a country to survive is to maintain the productive capacity of its economy, which reflects the efficient use of all resources, the quality of human capital and sustainable development. The essence and approaches to assessing the productive capacity of Ukraine, in particular according to the Productive Capacities Index (PCI), have been revealed. For the development of the European KLEMS productive capacity model, a formalized model and an approach to deepening its informational component are proposed. The factors of the “technological leap” that can be drivers of the development of productive capacity have been highlighted. The authors have proposed to consider productive capacity through the prism of sustainable development and its goals (SDGs). The “ecological footprint” has been described, which as of 2021 is 73% higher than the possibility of renewing the world’s ecosystems. The paper also covers a comprehensive approach to overcoming this risk (Twin-strategy) based on a combination of economic (but only within ecological) and social determinants of sustainable development. It has been noted that a bilateral “green” and “digital” strategy for the transition to the next stage of sustainable development (Twin Transitions for Global Value Chains) is relevant. A foresight approach to reducing gaps in the development of countries’ economies using advanced “green” technologies has been described.” It is summarized that in order to increase the productive capacity, Ukraine needs to rebuild the economy on the principles of Industry 4.0 with robotized production at “smart” factories. It has been studied that according to the Frontier Technologies Readiness Index, Ukraine belongs to the group of countries with an above-average level of the index. Recommendations on research and management of production potential for the reconstruction of Ukraine’s economy and its growth in the context of a bilateral “green” and “digital” strategy of sustainable development are given.